2013
DOI: 10.3109/08982104.2012.727423
|View full text |Cite
|
Sign up to set email alerts
|

Controlled drug-release system based on pH-sensitive chloride-triggerable liposomes

Abstract: New pH-sensitive lipids were synthesized and utilized in formulations of liposomes suitable for controlled drug release. These liposomes contain various amounts of NaCl in the internal aqueous compartments. The release of the drug model is triggered by an application of HCl cotransporter and exogenous physiologically relevant NaCl solution. HCl cotransporter allows an uptake of HCl by liposomes to the extent of their being proportional to the transmembrane Cl(-) gradient. Therefore, each set of liposomes under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Variation of the pKa of anionic lipids and their molar ratio can slightly modify the pH sensitivity. Another popular concept is based on the acidic hydrolysis of ortho-esters, acetals, hydrazones, vinyl ethers, or other acid-labile linkers in lipidic amphiphiles transforming the latter into destabilizing detergents or conical lipids (2,3,5,9,10,16,34,35). These reactions often require several hours to proceed, which may be a problem for timely drug release.…”
Section: Ph-responsive Systemsmentioning
confidence: 99%
“…Variation of the pKa of anionic lipids and their molar ratio can slightly modify the pH sensitivity. Another popular concept is based on the acidic hydrolysis of ortho-esters, acetals, hydrazones, vinyl ethers, or other acid-labile linkers in lipidic amphiphiles transforming the latter into destabilizing detergents or conical lipids (2,3,5,9,10,16,34,35). These reactions often require several hours to proceed, which may be a problem for timely drug release.…”
Section: Ph-responsive Systemsmentioning
confidence: 99%
“…1): (1) a cancer targeting moiety that can selectively guide the whole system into the tumor region; (2) an effector unit such as a reporter including fluorophore, an MRI contrast agent, and/or a pharmaceutical agent including a chemical drug, peptide, small interfering RNA (siRNA), or gene; and (3) a cleavable linker that is sufficiently stable to reduce cytotoxicity prior to its delivery to the target cells and cleaved enough to release its effector molecule upon arrival at the target and triggering by bio-species, pH, light, hypoxia, or other factors. [39][40][41] Recent studies demonstrated that thiol-containing amino acids, including glutathione (GSH), cysteine (Cys), and homocysteine (Hcy), are preferentially available in cancer cells to combat the gradual increase in reactive oxygen species (ROS) levels, maintaining the redox balance. Thus, a higher intracellular thiol concentration could be a characteristic element to distinguish between normal and cancer cells.…”
Section: Biotin-targeted Molecule Diagnostic and Therapeutic Systemsmentioning
confidence: 99%
“…Although the main focus of most studies carried out on pH-responsive liposomes, has been the pH-controlled disturbance of the membrane structure, there are studies on different mechanisms based on internal acidification of liposomes [127, 128]. More recently there have been several attempts performed to develop pH-labile liposomes for addressing multidrug resistance of cancer cells.…”
Section: Ph-sensitive Liposomesmentioning
confidence: 99%